Step
*
1
2
1
of Lemma
small-reciprocal-proof
1. e : ℚ
2. 0 < e
3. p : ℤ
4. q : ℤ
5. 0 < q
6. ¬(q = 0 ∈ ℚ)
7. e = (p/q) ∈ ℚ
8. ¬↑qeq(q;0)
9. 0 < p
10. q = (((q ÷ p) * p) + (q rem p)) ∈ ℤ
11. 0 ≤ (q rem p)
12. q rem p < p
13. 0 ≤ (q ÷ p)
⊢ (1/(q ÷ p) + 1) < (p/q)
BY
{ xxxxxxAssert ⌜q < ((q ÷ p) + 1) * p⌝⋅xxxxxx }
1
.....assertion..... 
1. e : ℚ
2. 0 < e
3. p : ℤ
4. q : ℤ
5. 0 < q
6. ¬(q = 0 ∈ ℚ)
7. e = (p/q) ∈ ℚ
8. ¬↑qeq(q;0)
9. 0 < p
10. q = (((q ÷ p) * p) + (q rem p)) ∈ ℤ
11. 0 ≤ (q rem p)
12. q rem p < p
13. 0 ≤ (q ÷ p)
⊢ q < ((q ÷ p) + 1) * p
2
1. e : ℚ
2. 0 < e
3. p : ℤ
4. q : ℤ
5. 0 < q
6. ¬(q = 0 ∈ ℚ)
7. e = (p/q) ∈ ℚ
8. ¬↑qeq(q;0)
9. 0 < p
10. q = (((q ÷ p) * p) + (q rem p)) ∈ ℤ
11. 0 ≤ (q rem p)
12. q rem p < p
13. 0 ≤ (q ÷ p)
14. q < ((q ÷ p) + 1) * p
⊢ (1/(q ÷ p) + 1) < (p/q)
Latex:
Latex:
1.  e  :  \mBbbQ{}
2.  0  <  e
3.  p  :  \mBbbZ{}
4.  q  :  \mBbbZ{}
5.  0  <  q
6.  \mneg{}(q  =  0)
7.  e  =  (p/q)
8.  \mneg{}\muparrow{}qeq(q;0)
9.  0  <  p
10.  q  =  (((q  \mdiv{}  p)  *  p)  +  (q  rem  p))
11.  0  \mleq{}  (q  rem  p)
12.  q  rem  p  <  p
13.  0  \mleq{}  (q  \mdiv{}  p)
\mvdash{}  (1/(q  \mdiv{}  p)  +  1)  <  (p/q)
By
Latex:
xxxxxxAssert  \mkleeneopen{}q  <  ((q  \mdiv{}  p)  +  1)  *  p\mkleeneclose{}\mcdot{}xxxxxx
Home
Index